Outcomes of Combined Visual and Auditive Stimulation on Functions of Hand and Grip Strengths in Patients with Hemiplegia - Baishya, Bhaswati; Varathan, Kalidasan (Journal of Health and Allied Sciences NU, 2022)
Background Stroke is a major ailment that results from hypoxia, ischemia, blockage, or hemorrhage. The recovery of hand functions is an essential goal in stroke patients' recovery.Aim This study aimed to analyze the outcomes of rhythmic auditory stimulation (RAS) and mirror therapy on hand functions, as well as grip strength, in stroke patients.Materials and Methods A quasiexperimental study has been used based on criteria of inclusion, 30 patients were enrolled. The participants were assigned to two groups, 15 patients each. Group A (control group) underwent traditional physiotherapy. Group B (experimental group) underwent RAS and mirror therapy. Both the groups received 20 minutes of treatment, 20 sessions in 1 month. The Action Research Arm Test (ARAT) and hand-held dynamometer were used to evaluate results. Paired t-test has been used to analyze the data with the SPSS software tool.Results The paired t-test results showed that notable distinctions in ARAT mean pretest scores between two groups were not found. A notable change in ARAT results was present between the two groups with mean posttest score and difference in pretest to posttest. No notable distinctions in grip strength results were seen with mean pretest results. But a notable change was found in grip strength results among two groups with mean posttest scores.Conclusion Combining RAS and mirror therapy programs has shown beneficial effects on hand functions, as well as grip strength of stroke patients and can be used as adjunct interventions along with conventional physiotherapy to encourage restoration of hand functions in hemiparetic patients.
Keywords: rhythmic auditory stimulation; mirror therapy; stroke; the action research arm test; grip strength